2019
DOI: 10.1093/pch/pxz073
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset neonatal sepsis: Organism patterns between 2009 and 2014

Abstract: Objective To evaluate trends in organisms causing early-onset neonatal sepsis (EONS). Congruent with recent reports, we hypothesized there would be an increase in EONS caused by Escherichia coli. Study Design National data on infants admitted to neonatal intensive care units from 2009 to 2014 were compared to previously reported data from 2003 to 2008. We report 430 cases of EONS from 2009 to 2014. Bivariate analyses were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Similar to previous studies neonates born by vaginal delivery were at a higher risk of neonatal sepsis compared with those delivered through Cesarean section [23,27]. Further, culture confirmed sepsis was high (89.9%) In this study, gram-negative bacteria were the most common cause of EOS and LOS, which is consistent with previous reports from developing countries [8,9,22,31]. Unexpectedly, B. cepacia emerged as the most common cause of neonatal sepsis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies neonates born by vaginal delivery were at a higher risk of neonatal sepsis compared with those delivered through Cesarean section [23,27]. Further, culture confirmed sepsis was high (89.9%) In this study, gram-negative bacteria were the most common cause of EOS and LOS, which is consistent with previous reports from developing countries [8,9,22,31]. Unexpectedly, B. cepacia emerged as the most common cause of neonatal sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Bacteria are the most common pathogens, and they vary in the distribution between countries, regions and according to the disease onset EOS versus LOS [7]. The commonly involved bacteria in developing countries include Klebsiella species, Staphylococcus aureus, E. coli, and Group B Streptococcus [8,9]. Recently, B. cepacia, a bacterial pathogen that has intrinsic drug resistance and ability to live inside drug products [10,11], has emerged as a significant pathogen causing neonatal sepsis [12][13][14][15][16].…”
mentioning
confidence: 99%
“… 1 In Canada, E. coli has surpassed group B Streptococcus (GBS) as the most common cause of EOS as screening and prophylactic intrapartum antibiotics have become the standard of care. 2 …”
Section: Introductionmentioning
confidence: 99%
“…1 In Canada, E. coli has surpassed group B Streptococcus (GBS) as the most common cause of EOS as screening and prophylactic intrapartum antibiotics have become the standard of care. 2 A number of risk factors for EOS have been identified, but the only recommendation is by the American Academy of Pediatrics (AAP) for asymptomatic siblings of a patient with EOS in a multigestational pregnancy is close observation, as EOS is usually caused by vertical transmission from the mother. 3 In a small case series and literature review, Almidani et al found a wide variation in practice and no consensus on management in this situation.…”
Section: Introductionmentioning
confidence: 99%
“…D espite significant advances in perinatal care, neonatal sepsis remains a predominant cause of morbidity and mortality in newborn infants, with group B streptococci (GBS) being one of the most common causative and clinically relevant pathogenic organisms. [1][2][3][4] Early-onset neonatal sepsis (EOS) is a life-threatening condition requiring prompt intravenous therapy with broad-spectrum antibiotics. Benzylpenicillin (BPEN), a time-dependent β-lactam antibiotic with narrow-spectrum activity, is the treatment of choice for the definitive treatment of GBS disease in newborn infants.…”
mentioning
confidence: 99%